Effect of vitamin D supplementation alone on muscle function in postmenopausal women: a randomized, double-blind, placebo-controlled clinical trial - Cangussu, L. M. [UNESP]; Nahas-Neto, J. [UNESP]; Orsatti, C. L. [UNESP]; Bueloni-Dias, F. N. [UNESP]; Nahas, E. A. P. [UNESP] (Spinger, 2015)
The present study investigates the effects of vitamin D on muscle function in postmenopausal women. It has been shown that vitamin D supplementation in postmenopausal women with hypovitaminosis D provides significant protective factor against sarcopenia, with significant increases in muscle strength and control of progressive loss of lean mass. We aimed to evaluate the effect of supplementation of vitamin D (VITD) alone on muscle function in younger postmenopausal women. In this double-blind, placebo-controlled clinical trial, 160 Brazilian postmenopausal women were randomized into two groups: VITD group consisting of patients receiving vitamin D3 1000 IU/day orally (n = 80) or placebo group (n = 80). Women with amenorrhea for more than 12 months and age 50-65 years, with a history of falls (previous 12 months), were included. The intervention time was 9 months, with assessments at two points, start and end. Lean mass was estimated by total-body dual-energy X-ray absorptiometry (DXA) and muscle strength by handgrip strength and chair rising test. The plasma concentrations of 25-hydroxyvitamin D [25(OH)D] were measured by high-performance liquid chromatography (HPLC). Statistical analysis was by intention to treat (ITT), using ANOVA, Student's t test, and Tukey's test. After 9 months, average values of 25(OH)D increased from 15.0 ± 7.5 to 27.5 ± 10.4 ng/ml (+45.4 %) in the VITD group and decreased from 16.9 ± 6.7 to 13.8 ± 6.0 ng/ml (-18.5 %) in the placebo group (p < 0.001). In the VITD group, there was significant increase in muscle strength (+25.3 %) of the lower limbs by chair rising test (p = 0.036). In women in the placebo group, there was considerable loss (-6.8 %) in the lean mass (p = 0.030). The supplementation of vitamin D alone in postmenopausal women provided significant protective factor against the occurrence of sarcopenia, with significant increases in muscle strength and control of progressive loss of lean mass.
Keywords: Lean mass; Menopause; Muscle function; Vitamin d